Javascript Bible, 4th Edition - Goodman, Danny (Hungry Minds, 2011)
Greatly enhanced and updated from the third edition, this is the title any JavaScripter cannot afford to be without! JavaScript Bible, 4th Edition covers the new powerful functionality JavaScript will gain with the release of new revs of Internet Explorer and Netscape Communicator. This book features essential new JS information, additional ready-to-use JavaScript applications, and scores of additional JavaScripts and Web page routines. As with the last edition, this book will bring non-technical professionals, including casual programmers and scripters, painlessly up to speed on all aspects of mastering JavaScript, including programming fundamentals, JavaScript language elements, and how to use them effectively, and how to easily and efficiently add powerful new functionality to HTML documents and Java applets.